2017
DOI: 10.1007/s00421-017-3563-7
|View full text |Cite
|
Sign up to set email alerts
|

Standing economy: does the heterogeneity in the energy cost of posture maintenance reside in differential patterns of spontaneous weight-shifting?

Abstract: Results Despite heterogeneity in EE response to steadystate standing, no differences were found in the amount or pattern of spontaneous weight-shifting between the two phenotypes. Whilst experimentally induced weight-shifting resulted in a mean EE increase of only 11% (range: 0-25%), intermittent leg/body displacement increased EE to >1.5 METs in all participants. Conclusions Although the variability in spontaneous weight-shifting signatures between individuals does not appear to underlie heterogeneity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
(51 reference statements)
4
17
1
Order By: Relevance
“…Whilst a certain amount of variability may be accounted for by differences in standardization and methodology, large levels of within-study variability (i.e., amongst individuals measured under identical experimental conditions) strongly suggests a large degree of true biological variability. Indeed the inter-individual variability shown in the early studies of Edholm et al (1955) and Passmore et al (1952), is almost identical to that which we have recently observed in our laboratory using contemporary equipment (Miles-Chan et al, 2013, 2017; Monnard and Miles-Chan, 2017)—i.e., ranging from individuals who showed no increase in EE during steady-state standing relative to sitting (“energy savers”) to those who showed sustained increases in EE of 25–35% (“energy spenders;” Figure 4). This is in sharp contrast to a relatively low intra-individual coefficient of variation in the energy cost of standing—reported by Miller to range from 4 to 7% (Miller, 1982), and the intra-individual coefficient of variation in EE during standing within our own laboratory to range from 0 to 7% (Miles-Chan et al, 2017).…”
Section: Energy Cost Of Posture Maintenancesupporting
confidence: 90%
See 4 more Smart Citations
“…Whilst a certain amount of variability may be accounted for by differences in standardization and methodology, large levels of within-study variability (i.e., amongst individuals measured under identical experimental conditions) strongly suggests a large degree of true biological variability. Indeed the inter-individual variability shown in the early studies of Edholm et al (1955) and Passmore et al (1952), is almost identical to that which we have recently observed in our laboratory using contemporary equipment (Miles-Chan et al, 2013, 2017; Monnard and Miles-Chan, 2017)—i.e., ranging from individuals who showed no increase in EE during steady-state standing relative to sitting (“energy savers”) to those who showed sustained increases in EE of 25–35% (“energy spenders;” Figure 4). This is in sharp contrast to a relatively low intra-individual coefficient of variation in the energy cost of standing—reported by Miller to range from 4 to 7% (Miller, 1982), and the intra-individual coefficient of variation in EE during standing within our own laboratory to range from 0 to 7% (Miles-Chan et al, 2017).…”
Section: Energy Cost Of Posture Maintenancesupporting
confidence: 90%
“…Indeed the inter-individual variability shown in the early studies of Edholm et al (1955) and Passmore et al (1952), is almost identical to that which we have recently observed in our laboratory using contemporary equipment (Miles-Chan et al, 2013, 2017; Monnard and Miles-Chan, 2017)—i.e., ranging from individuals who showed no increase in EE during steady-state standing relative to sitting (“energy savers”) to those who showed sustained increases in EE of 25–35% (“energy spenders;” Figure 4). This is in sharp contrast to a relatively low intra-individual coefficient of variation in the energy cost of standing—reported by Miller to range from 4 to 7% (Miller, 1982), and the intra-individual coefficient of variation in EE during standing within our own laboratory to range from 0 to 7% (Miles-Chan et al, 2017). Nevertheless, using standardized experimental conditions, we have yet to observe any difference in terms of sex (Miles-Chan et al, 2013, 2017) or ethnic group (Monnard and Miles-Chan, 2017) between these two EE phenotypes.…”
Section: Energy Cost Of Posture Maintenancesupporting
confidence: 90%
See 3 more Smart Citations